Exploring the Cardio-metabolic Relevance of T-cadherin: A Pleiotropic Adiponectin Receptor - L. Clark, Jaime; G. Taylor, Carla; Zahradka, Peter (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2017)
Background and Objective: T-cadherin is a unique member of the cadherin family and is primarily expressed in the cardiovascular system. T-cadherin has not been abundantly studied, but the studies conducted to date have explored the impact of this protein on health and the function of organs involved in metabolic regulation. Methods: This article examines the recent knowledge of the ligand partners for T-cadherin and the potential contribution(s) of T-cadherin to cardio-metabolic function. Result and Discussion: One significant role for T-cadherin is its ability to bind high molecular weight adiponectin in cardiovascular tissue, thereby mediating the cardio-protective benefits of adiponectin. It also has the ability to bind low-density lipoprotein via its glycosylphosphatidylinositol anchor; however, the exact physiological consequence of this ligand-receptor relationship is not known. T-cadherin appears to affect multiple conditions of cardio-metabolic disease, including atherosclerosis and insulin resistance. Research into T-cadherin has suggested that it may be useful as a diagnostic marker for the early stages of cardiovascular disease. However, with regard to insulin, T-cadherin is necessary for pancreatic insulin secretion, but overexpression of T-cadherin on vascular cells may promote endothelial insulin resistance. Conclusion: This review provides evidence that T-cadherin has an influential role on key cardiometabolic molecules and warrants further investigation.
Keywords: insulin